(untitled) (Research, Society and Development, 2022)
Oral Health Literacy (OHL) indicates the ability of people to obtain, process and understand basic information about oral health. The aim of this study was to evaluate the OHL levels of a multidisciplinary hospital team. A sociodemographic and occupational questionnaire and an OHL assessment instrument called Rapid Estimate of Adult Literacy in Brazilian Dentistry (BREALD-30) were used. 229 health professionals were interviewed. The convenience sample consisted of 51.1% female and 48.9% male. The mean age was 35 years (±7.9). Comparison of OHL level with sociodemographic and occupational data did not show statistical significance. When evaluating the associations between OHL and knowledge of oral pathologies and oral manifestations of systemic diseases, it was observed that the team knows how to detect halitosis (p=0.0421), sialorrhea (p=0.421) and knows the relationship of halitosis with systemic diseases (p=0.0423). Furthermore, it showed that training (p=0.0360) and the knowledge acquired during professional training (p=0.0394) do not interfere with OHL. There was a significant association between professionals who knew about the existence of the dental service at the hospital (p=0.0155). It is concluded that OHL is not used in patient care. These are important data, since it showed that, despite the high level of OHL, it is not knowledge added to the assistance provided by health professionals.